2022
DOI: 10.1007/s10787-022-00976-2
|View full text |Cite
|
Sign up to set email alerts
|

The effects of berberine on inflammatory markers in Chinese patients with metabolic syndrome and related disorders: a meta‑analysis of randomized controlled trials

Abstract: Background A meta-analysis of randomized controlled trials (RCTs) was conducted to systematically evaluate the effects of berberine on the inflammatory markers of metabolic syndrome (MetS) and related disorders. Method Databases that were searched from inception to October 2020 included PubMed, Web of Science, the Cochrane Library, CNKI, VIP, WanFang Data, and ClinicalTrials.gov. Two reviewers independently selected articles and extracted data. The pooled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…In addition, subgroup analysis showed that the significant results can be seen only in the subgroups with unhealthy metabolic status. This evidence can also be justified by the antiinflammatory properties of BBR (18,93,96). Moreover, risk of bias subgroup analysis has shown even in high risk of bias trials decreasing effect remained for all glycemic markers and even in most of them in moderate risk apart from HbA1c.…”
Section: E Ects Of Bbr On Fbgmentioning
confidence: 91%
See 4 more Smart Citations
“…In addition, subgroup analysis showed that the significant results can be seen only in the subgroups with unhealthy metabolic status. This evidence can also be justified by the antiinflammatory properties of BBR (18,93,96). Moreover, risk of bias subgroup analysis has shown even in high risk of bias trials decreasing effect remained for all glycemic markers and even in most of them in moderate risk apart from HbA1c.…”
Section: E Ects Of Bbr On Fbgmentioning
confidence: 91%
“…BBR was effective in reducing FBG only in the subgroup of FBG ≥100 which can be because of the induction of higher insulin secretion in hyperglycemia by BBR, as explained by a previous study (86). Another reason can be the anti-inflammatory properties of BBR (18,93,96) that result in FBG reduction only when it exceeds its normal range. Hyperglycemia induces oxidative stress (97) and BBR can act against the consequential inflammation.…”
Section: E Ects Of Bbr On Fbgmentioning
confidence: 99%
See 3 more Smart Citations